Status Kemitraan Dan Kompensasi Terhadap Kinerja Petugas Kurir Di Pt Pos Indonesia (Persero) Kcu Palembang - Saputra, Danny Wahyu; Mega Hastuti, Sri Wahyuni (Otonomi, 2026)
This study aims to analyze the effect of partnership status and compensation on the performance of courier officers at PT Pos Indonesia (Persero) KCU Palembang. The background of this study is based on the increasing competition in the logistics industry due to the development of e-commerce, which demands an increase in the quality of human resources, especially courier officers. The study used a quantitative method with a descriptive and associative approach. The research sample consisted of 79 courier officers selected through saturated sampling techniques. Data collection was carried out through observation, questionnaires, interviews, documentation, and literature studies. Data analysis used validity tests, reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and coefficients of determination (R²). The results showed that partnership status and compensation had a positive and significant effect, both partially and simultaneously, on courier officer performance. The coefficient of determination (R²) value of 0.611 indicates that 61.1% of the variation in courier officer performance can be explained by these two variables. This indicates that clarity of partnership status and fair compensation can increase motivation, loyalty, and productivity of courier officers. Researchers recommend that PT Pos Indonesia strengthen its partnership system and improve its compensation policy to improve the company's performance and competitiveness in the national logistics industry.